A sodium iron sulfate positive electrode material and preparation method thereof and sodium ion battery
Through the method of drying the drum scraper and calcining the protective atmosphere, the problems of high preparation cost and uneven materials of sodium ferrosulfate positive electrode materials are solved, and the uniform dispersion of conductive agents and the improvement of electrochemical performance are achieved. It is suitable for industrial applications of sodium ion batteries.
Patent Information
- Application Number
- CN202411719739.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-28
Smart Images

Figure CN119219065B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode materials and relates to a positive electrode material, in particular to a sodium iron sulfate positive electrode material and a preparation method thereof and a sodium ion battery. Background Art
[0002] The raw materials for the preparation of sodium ion batteries are abundant, evenly distributed and safer than lithium ion batteries. Therefore, it is of great significance to develop sodium ion batteries with low cost, safety, high energy density and long cycle life.
[0003] The positive electrode material of sodium-ion batteries affects the battery's operating voltage, energy density, cycle life and rate performance. Sodium iron sulfate positive electrode material has a higher operating voltage, long cycle life and higher thermal runaway temperature, and is expected to be applied on a large scale in the fields of energy storage and power batteries.
[0004] In the prior art, the main method for preparing sodium ferric sulfate cathode materials is ball milling, which has complicated steps for preparing precursors, and the obtained materials are easy to agglomerate, making it difficult to achieve uniform distribution of the materials. Spray drying can also achieve the preparation of sodium ferric sulfate cathode materials, but the thermal efficiency of spray drying is only 30%-50%, resulting in a high preparation cost of sodium ferric sulfate cathode materials.
[0005] Because providing a method for preparing sodium iron sulfate positive electrode material with low preparation cost and excellent electrochemical performance is of great significance for the industrial application of sodium ion batteries. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a sodium iron sulfate positive electrode material and a preparation method thereof and a sodium ion battery. The preparation method provided by the present invention can improve the dispersibility of the conductive agent in the positive electrode material and has low cost, which is conducive to the industrial production and application of the sodium iron sulfate positive electrode material.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a sodium iron sulfate positive electrode material, the preparation method comprising the following steps:
[0009] The sodium ferric sulfate precursor solution is dried by a roller scraper to obtain a precursor powder; the obtained precursor powder is calcined under protective atmosphere conditions to obtain the sodium ferric sulfate positive electrode material; the sodium ferric sulfate precursor solution includes a conductive agent, a dispersant, a reducing agent, a sodium source, an iron source and a solvent; the temperature of the roller scraper drying is 120°C to 200°C.
[0010] During the drying process of the sodium ferric sulfate precursor solution, the conductive agent is prone to secondary agglomeration. The present invention adopts a roller scraper drying method to dry the sodium ferric sulfate precursor solution. The roller scraper drying method has the characteristics of high thermal efficiency, fast drying speed and low cost. The conductive agent in the precursor powder after drying can be uniformly dispersed to the greatest extent, and the production cost of the sodium ferric sulfate positive electrode material can be reduced, which is beneficial to the industrial production and application of the sodium ferric sulfate positive electrode material.
[0011] The drum scraper drying of the present invention is carried out in a drum scraper dryer. For example, when the drum scraper dries the sodium iron sulfate precursor solution, the sodium iron sulfate precursor solution is transported to the surface of the rotating drum to form a liquid film, and the heat of the heating medium inside the drum is transferred to the liquid film through the drum wall in a heat conduction manner. During the rotation of the drum, the water in the sodium iron sulfate precursor solution gradually evaporates, and the dried material is scraped off by the scraper, completing the drum scraper drying.
[0012] Preferably, the scraper thickness of the roller scraper drying is 4 μm to 12 μm.
[0013] Preferably, the scraper speed of the roller scraper drying is 1 m / h to 2 m / h.
[0014] Preferably, the dispersant includes a first dispersant and a second dispersant.
[0015] The first dispersant includes sodium carboxymethyl cellulose; the second dispersant includes xanthan gum and / or sodium alginate.
[0016] Preferably, the mass ratio of the first dispersant to the second dispersant is 1:0.8 to 1:1.2.
[0017] Preferably, the solid content of the conductive agent in the solvent is 1.2 wt % to 2.5 wt %.
[0018] Preferably, the solid content of the dispersant in the solvent is 0.3 wt % to 1 wt %.
[0019] Preferably, the total solid content of the sodium source and the iron source in the solvent is 20 wt % to 40 wt %.
[0020] Preferably, the amount of the reducing agent is 2 wt % to 10 wt % of the iron source.
[0021] Preferably, the conductive agent includes any one of carbon nanotubes, carbon black or graphene oxide, or a combination of at least two of them.
[0022] Preferably, the reducing agent comprises ascorbic acid and / or citric acid.
[0023] Preferably, the sodium source comprises sodium sulfate.
[0024] Preferably, the iron source includes any one of anhydrous ferrous sulfate, ferrous sulfate monohydrate or ferrous sulfate heptahydrate, or a combination of at least two thereof.
[0025] Preferably, the calcination includes a first calcination and a second calcination performed sequentially.
[0026] The heating rate of the first calcination is 1.5°C / min to 2.5°C / min, the terminal temperature of the heating is 240°C to 270°C, and the holding time is 1.8h to 2.2h; the heating rate of the second calcination is 8°C / min to 12°C / min, the terminal temperature of the heating is 350°C to 400°C, and the holding time is 8h to 10h.
[0027] Preferably, the gas used for the protective atmosphere includes nitrogen and / or an inert gas.
[0028] In a second aspect, the present invention provides a sodium iron sulfate positive electrode material, and the sodium iron sulfate positive electrode material is prepared by the preparation method described in the first aspect.
[0029] In a third aspect, the present invention provides a sodium ion battery, comprising the sodium iron sulfate positive electrode material described in the second aspect.
[0030] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] During the drying process of the sodium ferric sulfate precursor solution, the conductive agent is prone to secondary agglomeration. The present invention adopts a roller scraper drying method to dry the sodium ferric sulfate precursor solution. The roller scraper drying method has the characteristics of high thermal efficiency, fast drying speed and low cost. The conductive agent in the precursor powder after drying can be uniformly dispersed to the greatest extent, and the production cost of the sodium ferric sulfate positive electrode material can be reduced, which is beneficial to the industrial production and application of the sodium ferric sulfate positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a SEM image of the sodium iron sulfate positive electrode material obtained in Example 1 of the present invention.
[0034] Figure 2 and Figure 3 This is a SEM image of the sodium iron sulfate positive electrode material obtained in Comparative Example 1 of the present invention.
[0035] Figure 4The XRD diagrams of the sodium iron sulfate positive electrode materials obtained in Example 1 of the present invention and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0037] A certain embodiment of the present invention provides a method for preparing a sodium iron sulfate positive electrode material, the preparation method comprising the following steps:
[0038] The sodium iron sulfate precursor solution is dried by a roller scraper to obtain a precursor powder; the obtained precursor powder is calcined under protective atmosphere conditions to obtain the sodium iron sulfate positive electrode material.
[0039] The sodium iron sulfate precursor solution comprises a conductive agent, a dispersant, a reducing agent, a sodium source, an iron source and a solvent.
[0040] The temperature of the roller scraper drying is 120°C to 200°C.
[0041] During the drying process of the sodium ferric sulfate precursor solution, the conductive agent is prone to secondary agglomeration. The present invention adopts a roller scraper drying method to dry the sodium ferric sulfate precursor solution. The roller scraper drying method has the characteristics of high thermal efficiency, fast drying speed and low cost. The conductive agent in the precursor powder after drying can be uniformly dispersed to the greatest extent, and the production cost of the sodium ferric sulfate positive electrode material can be reduced, which is beneficial to the industrial production and application of the sodium ferric sulfate positive electrode material.
[0042] The temperature of the roller scraper drying in the present invention is 120°C to 200°C, for example, it can be 120°C, 140°C, 150°C, 160°C, 180°C or 200°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] The drum scraper drying of the present invention is carried out in a drum scraper dryer. For example, when the drum scraper dries the sodium iron sulfate precursor solution, the sodium iron sulfate precursor solution is transported to the surface of the rotating drum to form a liquid film, and the heat of the heating medium inside the drum is transferred to the liquid film through the drum wall in a heat conduction manner. During the rotation of the drum, the water in the sodium iron sulfate precursor solution gradually evaporates, and the dried material is scraped off by the scraper, completing the drum scraper drying.
[0044] The appropriate scraper thickness can completely scrape the dried material off the drum surface to avoid the residual material affecting the next round of drying; however, a thicker scraper thickness will affect heat transfer and the drying efficiency. In order to ensure the drying efficiency and smooth drying, the scraper thickness needs to be optimally set.
[0045] In some embodiments, the scraper thickness of the roller scraper drying is 4μm to 12μm, for example, it can be 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 12μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some embodiments, the scraper speed of the roller scraper drying is 1m / h to 2m / h, for example, it can be 1m / h, 1.2m / h, 1.5m / h, 1.8m / h or 2m / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] The present invention adopts a roller scraper drying method for drying, which has the characteristics of high heat-selling efficiency and can complete drying in about 3 seconds, thereby ensuring the uniformity of dispersion of the conductive agent.
[0048] In certain embodiments, the dispersant includes a first dispersant and a second dispersant.
[0049] The first dispersant includes sodium carboxymethyl cellulose; the second dispersant includes xanthan gum and / or sodium alginate.
[0050] In certain embodiments, the dispersant includes sodium carboxymethyl cellulose and xanthan gum.
[0051] The first dispersant and the second dispersant can play a synergistic role, so that they can still exert good dispersing performance under the acidic conditions caused by the reducing agent; moreover, they can also play a role in stabilizing the slurry during roller scraper drying and maintain a good film-forming effect during the roller scraper drying process; the first dispersant and the second dispersant provide a three-dimensional network structure, which on the one hand fully guarantees the dispersibility of the conductive agent, thereby improving the conductive properties of the sodium iron sulfate positive electrode material; on the other hand, it increases the Na ion vacancies during the calcination process and improves the rate performance.
[0052] In certain embodiments, the mass ratio of the first dispersant to the second dispersant is 1:0.8 to 1:1.2, for example, 1:0.8, 1:0.9, 1:1, 1:1.1 or 1:1.2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In some embodiments, the solid content of the conductive agent in the solvent is 1.2wt% to 2.5wt%, for example, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.1wt%, 2.4wt% or 2.5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In certain embodiments, the solid content of the dispersant in the solvent is 0.3 wt % to 1 wt %, for example, 0.3 wt %, 0.4 wt %, 0.5 wt %, 0.6 wt %, 0.8 wt % or 1 wt %, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In certain embodiments, the total solid content of the sodium source and the iron source in the solvent is 20 wt % to 40 wt %, for example, 20 wt %, 25 wt %, 28 wt %, 30 wt %, 32 wt %, 35 wt %, 38 wt % or 40 wt %, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In certain embodiments, the amount of the reducing agent is 2 wt% to 10 wt% of the iron source, for example, 2 wt%, 4 wt%, 5 wt%, 6 wt%, 8 wt% or 10 wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In certain embodiments, the conductive agent includes any one of carbon nanotubes, carbon black or graphene oxide, or a combination of at least two of them. Typical but non-limiting combinations include a combination of carbon nanotubes and carbon black, a combination of carbon nanotubes and graphene oxide, a combination of carbon black and graphene oxide, or a combination of carbon nanotubes, carbon black and graphene oxide.
[0058] In certain embodiments, the reducing agent comprises ascorbic acid and / or citric acid.
[0059] In certain embodiments, the sodium source comprises sodium sulfate.
[0060] In certain embodiments, the iron source includes any one of anhydrous ferrous sulfate, ferrous sulfate monohydrate, or ferrous sulfate heptahydrate, or a combination of at least two thereof.
[0061] In certain embodiments, in the sodium iron sulfate precursor solution, the molar ratio of sodium in the sodium source to iron in the iron source is 1:1 to 2:1, for example, 1:1, 1.2:1, 1.5:1, 1.6:1, 1.8:1 or 2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In certain embodiments, the solvent comprises water.
[0063] In certain embodiments, the calcination includes a first calcination and a second calcination performed sequentially.
[0064] The heating rate of the first calcination is 1.5°C / min to 2.5°C / min, the terminal temperature of the heating is 240°C to 270°C, and the holding time is 1.8h to 2.2h; the heating rate of the second calcination is 8°C / min to 12°C / min, the terminal temperature of the heating is 350°C to 400°C, and the holding time is 8h to 10h.
[0065] In the present invention, the heating rate of the first calcination is 1.5°C / min to 2.5°C / min, for example, it can be 1.5°C / min, 1.8°C / min, 2°C / min, 2.2°C / min or 2.5°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In the present invention, the heating end point temperature of the first calcination is 240°C to 270°C, for example, it can be 240°C, 245°C, 250°C, 255°C, 260°C, 265°C or 270°C, but is not limited to the listed values, and the remaining unlisted values within the numerical range are also applicable.
[0067] In the present invention, the holding time of the first calcination is 1.8 h to 2.2 h, for example, 1.8 h, 1.9 h, 2 h, 2.1 h or 2.2 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0068] In the present invention, the heating rate of the second calcination is 8°C / min to 12°C / min, for example, it can be 8°C / min, 9°C / min, 10°C / min, 11°C / min or 12°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] In the present invention, the end temperature of the second calcination is 350°C to 400°C, for example, 350°C, 360°C, 380°C, 390°C or 400°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] In the present invention, the holding time of the second calcination is 8 h to 10 h, for example, 8 h, 8.5 h, 9 h, 9.5 h or 10 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0071] In some embodiments, the protective atmosphere includes nitrogen and / or an inert gas.
[0072] A certain embodiment of the present invention provides a sodium iron sulfate positive electrode material, and the sodium iron sulfate positive electrode material is prepared by the preparation method described in any embodiment.
[0073] The structural formula of the sodium iron sulfate positive electrode material obtained by the present invention is Na x Fe(SO4) y / C, where 0 <x≤3,y=(2+x) / 2。
[0074] A certain embodiment of the present invention provides a sodium ion battery, wherein the sodium ion battery comprises the sodium iron sulfate positive electrode material described in any embodiment.
[0075] The xanthan gum used in the examples and comparative examples of the present invention was purchased from Fufeng, A6250, and its viscosity at 25° C. and relative humidity of 52% was 1752 cP. The above description of xanthan gum is only for the purpose of clearly illustrating the technical solution of the present invention and is not to be regarded as further limiting the present invention.
[0076] Example 1
[0077] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, the preparation method comprising the following steps:
[0078] (1) Mix sodium carboxymethyl cellulose, xanthan gum and water, and stir until they are completely dissolved; the mass ratio of sodium carboxymethyl cellulose to xanthan gum is 1:1, and the total solid content of sodium carboxymethyl cellulose and xanthan gum in water is 0.5 wt %.
[0079] (2) Continue to add conductive carbon nanotubes, where the solid content of the conductive agent in water is 2 wt %, and perform ultrasonic dispersion for 90 min to obtain a dispersion.
[0080] (3) Adding reducing agent ascorbic acid, anhydrous sodium sulfate and ferrous sulfate heptahydrate to the dispersion, and mechanically stirring for 1 hour at a rotation speed of 550 rpm to obtain a sodium ferric sulfate precursor solution; the total solid content of anhydrous sodium sulfate and ferrous sulfate heptahydrate in water is 35 wt%, and the molar ratio of sodium to iron is 1.34:1; the amount of reducing agent ascorbic acid used is 5 wt% of ferrous sulfate heptahydrate.
[0081] (4) The sodium iron sulfate precursor solution was coated on a release film, and was subjected to roller scraper drying at a scraper thickness of 8 μm, a scraper speed of 1 m / h, and a temperature of 150° C. to obtain a precursor powder.
[0082] (5) In a nitrogen atmosphere, the precursor powder was subjected to a first calcination and a second calcination in sequence to obtain a sodium iron sulfate positive electrode material. The heating rate of the first calcination was 2°C / min, the end temperature of the heating was 250°C, and the holding time was 2h; the heating rate of the second calcination was 10°C / min, the end temperature of the heating was 370°C, and the holding time was 9h.
[0083] The SEM image of the sodium iron sulfate positive electrode material obtained in this example is as follows Figure 1 As shown, the XRD pattern is Figure 4 shown.
[0084] Example 2
[0085] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, the preparation method comprising the following steps:
[0086] (1) Mix sodium carboxymethyl cellulose, xanthan gum and water and stir until they are completely dissolved; the mass ratio of sodium carboxymethyl cellulose to xanthan gum is 1:0.8, and the total solid content of sodium carboxymethyl cellulose and xanthan gum in water is 0.3 wt %.
[0087] (2) Continue to add conductive carbon nanotubes, where the solid content of the conductive agent in water is 1.2 wt %, and perform ultrasonic dispersion for 90 min to obtain a dispersion.
[0088] (3) Adding reducing agent ascorbic acid, anhydrous sodium sulfate and ferrous sulfate heptahydrate to the dispersion, and mechanically stirring for 1 hour at a rotation speed of 550 rpm to obtain a sodium ferric sulfate precursor solution; the total solid content of anhydrous sodium sulfate and ferrous sulfate heptahydrate in water is 20wt%, and the molar ratio of sodium to iron is 1.34:1; the amount of reducing agent ascorbic acid is 2wt% of ferrous sulfate heptahydrate.
[0089] (4) The sodium iron sulfate precursor solution was coated on a release film, and then dried by roller scraper at a scraper thickness of 8 μm, a scraper speed of 1 m / h, and a temperature of 120° C. to obtain a precursor powder.
[0090] (5) In a nitrogen atmosphere, the precursor powder was subjected to a first calcination and a second calcination in sequence to obtain a sodium iron sulfate positive electrode material. The heating rate of the first calcination was 1.5°C / min, the end temperature of the heating was 240°C, and the holding time was 2.2h; the heating rate of the second calcination was 8°C / min, the end temperature of the heating was 350°C, and the holding time was 10h.
[0091] Example 3
[0092] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, the preparation method comprising the following steps:
[0093] (1) Mix sodium carboxymethyl cellulose, xanthan gum and water and stir until they are completely dissolved; the mass ratio of sodium carboxymethyl cellulose to xanthan gum is 1:1.2, and the total solid content of sodium carboxymethyl cellulose and xanthan gum in water is 1 wt %.
[0094] (2) Continue to add conductive carbon nanotubes, where the solid content of the conductive agent in water is 2.5 wt %, and perform ultrasonic dispersion for 90 min to obtain a dispersion.
[0095] (3) Adding reducing agent ascorbic acid, anhydrous sodium sulfate and ferrous sulfate heptahydrate to the dispersion, and mechanically stirring for 1 hour at a rotation speed of 550 rpm to obtain a sodium ferric sulfate precursor solution; the total solid content of anhydrous sodium sulfate and ferrous sulfate heptahydrate in water is 40wt%, and the molar ratio of sodium to iron is 1.34:1; the amount of reducing agent ascorbic acid is 10wt% of ferrous sulfate heptahydrate.
[0096] (4) The sodium iron sulfate precursor solution was coated on a release film, and then dried by roller scraper at a scraper thickness of 8 μm, a scraper speed of 2 m / h, and a temperature of 200° C. to obtain a precursor powder.
[0097] (5) In a nitrogen atmosphere, the precursor powder was subjected to a first calcination and a second calcination in sequence to obtain a sodium iron sulfate positive electrode material. The heating rate of the first calcination was 2.5°C / min, the end temperature of the heating was 270°C, and the holding time was 1.8h; the heating rate of the second calcination was 12°C / min, the end temperature of the heating was 400°C, and the holding time was 8h.
[0098] Example 4
[0099] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, which is the same as that of Embodiment 1 except that xanthan gum is replaced by sodium alginate.
[0100] Example 5
[0101] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, which is the same as that of Embodiment 1 except that the thickness of the scraper used in the roller scraper drying is 4 μm.
[0102] Example 6
[0103] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, which is the same as that of Embodiment 1 except that the thickness of the scraper used in the roller scraper drying is 10 μm.
[0104] Example 7
[0105] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, which is the same as that of Embodiment 1 except that the thickness of the scraper used in the roller scraper drying is 12 μm.
[0106] Example 8
[0107] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, which is the same as that of Embodiment 1 except that the mass of sodium carboxymethyl cellulose is replaced by xanthan gum, that is, the dispersant is only xanthan gum.
[0108] Example 9
[0109] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, which is the same as that of Embodiment 1 except that the xanthan gum is replaced by sodium carboxymethyl cellulose, that is, the dispersant is only sodium carboxymethyl cellulose.
[0110] Example 10
[0111] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, which is the same as that of Embodiment 1 except that the mass of xanthan gum and sodium carboxymethyl cellulose is replaced by sodium alginate, that is, the dispersant is only sodium alginate.
[0112] Comparative Example 1
[0113] This comparative example provides a method for preparing a sodium iron sulfate positive electrode material, the preparation method comprising the following steps:
[0114] (1) Mix sodium carboxymethyl cellulose, xanthan gum and water, and stir until they are completely dissolved; the mass ratio of sodium carboxymethyl cellulose to xanthan gum is 1:1, and the total solid content of sodium carboxymethyl cellulose and xanthan gum in water is 0.5 wt %.
[0115] (2) Continue to add conductive carbon nanotubes, where the solid content of the conductive agent in water is 2 wt %, and perform ultrasonic dispersion for 90 min to obtain a dispersion.
[0116] (3) Adding reducing agent ascorbic acid, anhydrous sodium sulfate and ferrous sulfate heptahydrate to the dispersion, and mechanically stirring for 1 hour at a rotation speed of 550 rpm to obtain a sodium ferric sulfate precursor solution; the total solid content of anhydrous sodium sulfate and ferrous sulfate heptahydrate in water is 35 wt%, and the molar ratio of sodium to iron is 1.34:1; the amount of reducing agent ascorbic acid used is 5 wt% of ferrous sulfate heptahydrate.
[0117] (4) The sodium iron sulfate precursor solution is spray-dried at 200° C. to obtain a precursor powder.
[0118] (5) In a nitrogen atmosphere, the precursor powder was subjected to a first calcination and a second calcination in sequence to obtain a sodium iron sulfate positive electrode material. The heating rate of the first calcination was 2°C / min, the end temperature of the heating was 250°C, and the holding time was 2h; the heating rate of the second calcination was 10°C / min, the end temperature of the heating was 370°C, and the holding time was 9h.
[0119] The SEM image of the sodium iron sulfate positive electrode material obtained in this comparative example is as follows Figure 2 , Figure 3 As shown, the XRD pattern is Figure 4 shown.
[0120] Performance Testing
[0121] The sodium iron sulfate positive electrode material, carbon black, and polyvinylidene fluoride (PVDF) obtained in the above embodiment and the comparative example were mixed in a mass ratio of 90:5:5, and coated on aluminum foil using a 100μm four-sided preparation device, and then the electrode film was pre-dried in an 80°C blast drying oven for 30min, and then transferred to a vacuum drying oven at 110°C for drying for 10 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, and sodium metal was used as the counter electrode, 1mol / LNaClO4 EC+DEC (1:1vol%) +5%FEC was used as the electrolyte, and a Whatman-D glass fiber diaphragm was used to assemble a CR2032 type button battery in a glove box. EC is ethylene carbonate, DEC is diethyl carbonate, and FEC is fluoroethylene carbonate.
[0122] The obtained button cell was subjected to constant current charge and discharge tests in the voltage range of 2.5V to 4.3V, with a current density of 0.1C (1C=100mAh / g). The rate performance was tested at 0.2C, 0.5C, 1C, 2C, 5C and 10C. The results are shown in Table 1.
[0123] Table 1
[0124]
[0125] In summary, during the drying process of the sodium ferric sulfate precursor solution, the conductive agent is prone to the defect of secondary agglomeration. The present invention adopts a roller scraper drying method to dry the sodium ferric sulfate precursor solution. By utilizing the characteristics of high thermal efficiency, fast drying speed and low cost of roller scraper drying, the conductive agent in the precursor powder after drying can be uniformly dispersed to the greatest extent, and the production cost of the sodium ferric sulfate positive electrode material can be reduced, which is beneficial to the industrial production and application of the sodium ferric sulfate positive electrode material.
[0126] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a sodium iron sulfate positive electrode material, characterized in that: The preparation method comprises the following steps: The sodium iron sulfate precursor solution is dried by a roller scraper to obtain a precursor powder; the obtained precursor powder is calcined under protective atmosphere conditions to obtain the sodium iron sulfate positive electrode material; The sodium iron sulfate precursor solution comprises a conductive agent, a dispersant, a reducing agent, a sodium source, an iron source and a solvent; The temperature of the roller scraper drying is 120°C to 200°C.
2. The preparation method according to claim 1, characterized in that: The scraper thickness of the roller scraper drying is 4 μm to 12 μm; And / or, the scraper speed of the roller scraper drying is 1 m / h to 2 m / h.
3. The preparation method according to claim 1, characterized in that: The dispersant includes a first dispersant and a second dispersant; The first dispersant includes sodium carboxymethyl cellulose; The second dispersant includes xanthan gum and / or sodium alginate.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the first dispersant to the second dispersant is 1:0.8 to 1:1.
2.
5. The preparation method according to claim 1, characterized in that: The solid content of the conductive agent in the solvent is 1.2wt% to 2.5wt%; and / or, the solid content of the dispersant in the solvent is 0.3 wt % to 1 wt %; and / or, the total solid content of the sodium source and the iron source in the solvent is 20wt% to 40wt%; And / or, the reducing agent is used in an amount of 2 wt % to 10 wt % of the iron source.
6. The preparation method according to claim 1, characterized in that: The conductive agent includes any one of carbon nanotubes, carbon black or graphene oxide, or a combination of at least two thereof; and / or, the reducing agent comprises ascorbic acid and / or citric acid; and / or, the sodium source comprises sodium sulfate; And / or, the iron source includes any one of anhydrous ferrous sulfate, ferrous sulfate monohydrate or ferrous sulfate heptahydrate, or a combination of at least two thereof.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The calcination includes a first calcination and a second calcination performed sequentially; The first calcination has a heating rate of 1.5°C / min to 2.5°C / min, a heating end point temperature of 240°C to 270°C, and a holding time of 1.8h to 2.2h; The heating rate of the second calcination is 8°C / min to 12°C / min, the heating end point temperature is 350°C to 400°C, and the holding time is 8h to 10h.
8. The preparation method according to claim 1, characterized in that: The gas used in the protective atmosphere includes nitrogen and / or an inert gas.
9. A sodium iron sulfate positive electrode material, characterized in that: The sodium iron sulfate positive electrode material is prepared by the preparation method according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium iron sulfate positive electrode material according to claim 9.
Citation Information
Patent Citations
Positive electrode material of lithium ion battery, and preparation method thereof
CN104201370A
Scraping plate drum dryer
CN105588407A